Religion and Media, Religious Media, or Media Religion: Theoretical Studies - Hosseini, S. H. (Journal of media and religion, 2008)
Major efforts have been exhausted bringing religion closer to media (rather than bringing media closer to religion), or to break down the traditional boundaries between the "religious" and the "media." In light of such efforts and various research, some have tried to show the necessity of building new bridges between religion and media. These attempts have even made scholars believe that in the "media age," the secular is sacred and the sacred is secular. This endeavor was aimed at the unification of the two important elements of contemporary human life, which historically could also be understood in the context of challenging the relationship between science and religion. In this paper, I have tried to classify the various theories and approaches about the essence of the media in three branches: functionalistic, essentialist, and interactive hypotheses. After a short review of the consequences of each theory's compatibility or incompatibility with media, religion, and religious teachings, I demonstrate that a more fundamental step should be taken to combine religion and media in an era known as the "Global," "Religious," or "Media Age." The other part of the paper is devoted to the necessary distinction between religious media and mediated religion, emphasizing the main characteristics of religious media theory. Although the basic principle of media essentialism has been accepted, religion, which is neither the institutional ministry nor an absolute personal experience, has the potential to be consistent with the exclusive nature of the media. The final part of the article points to the focal axis of the religious media hypothesis within which elements of religion, culture, globalization, and the media are balanced and stabilized. This is religious pluralism.